A meta-analysis of cerebrocerebellar networks of reading and working memory - Soh, Valeree (Nanyang Technological University, 2024)
The cerebellum is steadily gaining recognition as being integral to cognition. This meta-analysis investigated consistently activated cortical and cerebellar regions, and cerebrocerebellar functional connectivity networks for reading and working memory. Activation Likelihood Estimation meta-analysis was used on task-based fMRI and PET studies involving these domains. Consistent activation was observed in the left inferior frontal gyrus and fusiform gyrus during reading, while working memory revealed a fronto-parietal activation pattern with bilateral cerebellar Lobule VI/Crus I involvement. Previously underexplored regions were also activated. Furthermore, functional connectivity networks of reading revealed a hierarchical pattern, with the left IFG at the top. Functional connectivity networks of working memory found extensive connections involving the left lentiform nucleus, underscoring its potentially significant role in supporting working memory. Furthermore, bilateral cerebellar Lobule VI, right cerebellar Crus II, and left cerebellar Crus I were commonly activated in both processes. The study concluded by highlighting the importance of understanding neural mechanisms underlying specific aspects of reading and WM, proposing that regions showing activation and functional connectivity networks differ based on task specificity.